Optimization time and mass of eggshell adsorbent in improving waste cooking oil quality - Sani Widyastuti Pratiwi; Srie Gustiani; Kenanga Triulfa Amadea; Ratna Nurmalasari; Inggis Pinarti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Oxidation and hydrolysis damage to cooking oil can occur due to repeated use of cooking oil. Adsorption by utilizing eggshells, which contain high calcium carbonate and have a natural pore structure that can improve the quality of used cooking oil. This study aims to determine the physical properties and characteristics of the thermally activated chicken eggshell adsorbent and to determine the ability of the adsorbent to absorb acid and metal cadmium. The steps carried out in this study were the manufacture of adsorbents, quality tests of the adsorbents produced, and testing of adsorbents on used cooking oil samples based on acid numbers and decreasing levels of metal cadmium in the samples. The adsorption process of used cooking oil was carried out with variations in the mass of the adsorbent, namely 5, 7, 9, and 11 grams, and stirring time for 10, 20, 40, and 60 minutes. Based on the results of the study, it was found that the optimum conditions for decreasing the acid number with the use of an adsorbent mass of 11 grams and a stirring time of 60 minutes resulted in an acid number was 0.9974 mg NaOH/g with a decrease in the acid number of 76.54%, while for cadmium metal it decreased by 100% with adsorption capacity of 2.57124 mg/g.